2011
DOI: 10.1111/j.1365-2435.2011.01867.x
|View full text |Cite
|
Sign up to set email alerts
|

Functional specialization of Eucalyptus fine roots: contrasting potential uptake rates for nitrogen, potassium and calcium tracers at varying soil depths

Abstract: Summary 1.Little is known about the role of deep roots in the nutrition of forest trees and their ability to provide a safety-net service taking up nutrients leached from the topsoil. 2. To address this issue, we studied the potential uptake of N, K and Ca by Eucalyptus grandis trees (6 years of age -25 m mean height), in Brazil, as a function of soil depth, texture and water content. We injected NO ) tracers simultaneously in a solution through plastic tubes at 10, 50, 150 and 300 cm in depth in a sandy and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
51
0
8

Year Published

2011
2011
2020
2020

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 89 publications
(64 citation statements)
references
References 61 publications
5
51
0
8
Order By: Relevance
“…The model efficiency amounted to 0.66 for the low P treatment and 0.97 for the high P treatment, showing substantial underestimation of the observed P uptake at low P supply (from Mollier et al (2008), reprinted with permission from Elsevier BV) architecture, in spite of its importance in resource exploitation efficiency (Fitter et al 1991). In particular, the contribution of very deep roots on water and nutrient uptake in natural and agroecosystems established on highly weathered tropical soils is still poorly known (Battie-Laclau and Laclau 2009; Christina et al 2011;Jackson et al 2000;Schenk and Jackson 2002;Silva et al 2011). Nevertheless, root architecture models have proved useful for predicting water uptake (Doussan et al 1998(Doussan et al , 1999(Doussan et al , 2003(Doussan et al , 2006Pagès et al 2004;Pierret et al 2007), localizing nutrient uptake zones or describing situations of heterogeneous distribution of nutrients in the soil profile (Ge et al 2000;Liao et al 2001;Lynch and Brown 2001;Rubio et al 2003).…”
Section: Why and Which Plant Nutrition Models What For?mentioning
confidence: 96%
“…The model efficiency amounted to 0.66 for the low P treatment and 0.97 for the high P treatment, showing substantial underestimation of the observed P uptake at low P supply (from Mollier et al (2008), reprinted with permission from Elsevier BV) architecture, in spite of its importance in resource exploitation efficiency (Fitter et al 1991). In particular, the contribution of very deep roots on water and nutrient uptake in natural and agroecosystems established on highly weathered tropical soils is still poorly known (Battie-Laclau and Laclau 2009; Christina et al 2011;Jackson et al 2000;Schenk and Jackson 2002;Silva et al 2011). Nevertheless, root architecture models have proved useful for predicting water uptake (Doussan et al 1998(Doussan et al , 1999(Doussan et al , 2003(Doussan et al , 2006Pagès et al 2004;Pierret et al 2007), localizing nutrient uptake zones or describing situations of heterogeneous distribution of nutrients in the soil profile (Ge et al 2000;Liao et al 2001;Lynch and Brown 2001;Rubio et al 2003).…”
Section: Why and Which Plant Nutrition Models What For?mentioning
confidence: 96%
“…The differences in nutrients concentrations in the soil profile can be related to the uptake rates and the trees growth. Silva et al (2011) evaluating Eucalyptus grandis plantations observed that the fine roots exhibit contrasting potential uptake rates with depth depending on the nutrient. These authors suggest that, the roots specialization might contribute to the high growth rates of the trees and efficiently providing the nutrients required in their development.…”
Section: Resultsmentioning
confidence: 99%
“…In fast-growing plantations the potential uptake rates depends on the functional specialization of roots (SILVA et al, 2011). Mareschal et al (2013) studied the effect to eucalyptus plantations managed in short rotations after afforestation of an African savanna.…”
Section: Introductionmentioning
confidence: 99%
“…El aumento generalizado de potasio en la profundidad 0-20 cm observado en la Figura 1 podría estar relacionado por un lado a la capacidad mostrada por las raíces profundas de Eucalyptus spp, las cuales presentan grandes potencialidades en la absorción del potasio (Da Silva et al, 2011) lo por lo que la especie podría estar extrayendo potasio en profundidad y depositándolo, vía hojarasca, en la parte superior del suelo, este sería un motivo por el cual una adecuada preparación de sitio, como la realizada en este caso, podría promover el desarrollo radicular en profundidad siendo esta una estrategia para la obtención de potasio, por los árboles, en estas plantaciones.…”
Section: Eficiencia Nutricionalunclassified